Asset correlation and international portfolio diversification benefit / Noor Azida Abu Bakar - Abu Bakar, Noor Azida (2011)
Most of the investors apply international diversification in their investment to gain higher return with low risk as well as. Financial economists recommend adding international assets to portfolios because they actually reduce risk. The reason is that international assets don’t move in perfect tandem with domestic assets. On the other hand, the main objectives of this research are to find out the main purposes of asset correlation and benefit from international diversification. It is beneficial to investor to gain higher return at lower risk. For this purpose, 23 global world indices have been selected as my main data for this research of asset correlation and international diversification benefits. Besides, the higher the correlation, the lower the diversification benefits. However, as long as the correlations are not +1, then there is some diversification benefit. Obviously the lower the correlations, the larger the benefit. This is because, whenever there is a financial crisis some hear the nonsense that diversification doesn't work, correlations rise towards one at the worst time. The fact that correlations of all risky assets tends to move toward 1 whenever systemic crises have doesn't mean diversification doesn't work. What it means is that the most important diversification is the decision on how much fixed income one holds. Risky fixed income investments see correlations rise at the worst times, while with safe assets the correlations tend to move in the other direction during crises. Furthermore, even though correlations of risky assets tend to rise during crises, after the crises is resolved the correlations tend to drift back to historical averages which is in other words investors need to know that correlations are not static. For example of this is to look at returns of various asset classes in 2009 and this year. After the crises, a wide dispersion of returns across risky assets once again. Therefore, make sure the investors stay disciplined and rebalance, to gain the benefits of diversification